MANFAAT INDIKATOR-INDIKATOR KEUANGAN DALAM PEMBENTUKAN MODEL PREDIKSI KONDISI KESEHATAN PERBANKAN - Sugiyanto, FX; Prasetiono, Prasetiono; Hariyanto, Teddy (JURNAL BISNIS STRATEGI, 2002)
Financial distress prediction is an essential issue in finance. Especially in emerging economies, predicting the future financial situation of individual corporate entities is even more significant, bearing in mind the general economic turnrr.oil that can be caused by business failures. Following this discrimination approach this study explores the usefulness of financial ratios in constructing the discrimination models as an early waring system. Theratios used in the models were compiled from financial report: of 11 oIndonesian banks that listed in Indonesian Banking Directory. The result ofthis investigation show that financial ratios ara significant within 5% for one year before failure and 10% for two years before failure as bankruptcy prediction variable of a bank. Those ratios also explain that asset quality, management earning power and liquidity are the determines of the Indonesian banks banckruptcy.